Patient-Reported Effectiveness of Proactive Psychiatric Care in Patients with Chronic Pain: A SPAASMS-Based Assessment - Asanova Азізе (Psychosomatic Medicine and General Practice, 2026)
Background. Contemporary approaches to chronic pain management extend beyond the assessment of pain intensity alone and increasingly emphasize a broader range of outcomes reflecting functional status, psychological well-being and patient’s subjective perception of treatment effectiveness. Consequently, the use of comprehensive assessment tools has become increasingly important for evaluating the effectiveness of multimodal chronic pain treatment programs. Objective. To evaluate the impact of proactive psychiatric support on pain perception, functional status, and psychological well-being in patients with chronic pain using the SPAASMS scale. Methods. A prospective cohort clinical psychopathological study was conducted involving 302 patients with chronic pain who completed a personalized multimodal treatment program delivered within the framework of proactive psychiatric support. According to a psychiatric-oriented stratification model, patients were allocated to five groups: primary psychogenic pain (PPP1), primary psychophysiological pain (PPP2), mixed primary psychogenic and psychophysiological pain (PPP3), secondary mixed pain (SMP) and secondary organic pain (SOP). Mental disorders were verified according to ICD-10 diagnostic criteria, with subsequent alignment of diagnoses with ICD-11. Subjective pain-related outcomes were assessed using the SPAASMS scale at baseline and after 12 months after treatment initiation. Statistical analyses were performed using RStudio. Data normality was assessed with the Shapiro–Wilk test, and repeated measures were analyzed using the Friedman test. A p-value <0.05 was considered statistically significant. Results. Following completion of proactive psychiatric support, a statistically significant reduction in total SPAASMS scores was observed across all study groups (p<0.001). The most pronounced improvement was found in the PPP1 and PPP3 groups, where total SPAASMS scores decreased 5.7-fold and 4.2-fold, respectively. All groups demonstrated significant reductions in pain intensity, accompanied by improvements in physical activity, sleep quality, and mood, as well as decreased reliance on additional analgesic medications and fewer healthcare visits related to pain. A reduction in treatment-related adverse effects was also observed. The least pronounced improvement in pain-related outcomes was found in the SOP group. Conclusions. Proactive psychiatric support was associated with significant improvements in patient-reported pain outcomes across all SPAASMS domains. The greatest clinical benefit was observed among patients with primary psychogenic pain and mixed primary psychogenic and psychophysiological pain, highlighting the importance of psychopathological mechanisms in shaping the subjective experience of chronic pain and supporting the integration of proactive psychiatric care into multimodal treatment programs. Keywords: chronic pain, patient-reported effectiveness, SPAASMS, psychiatric care, multimodal treatment, psychosomatic medicine.